2023
DOI: 10.1161/jaha.122.028511
|View full text |Cite
|
Sign up to set email alerts
|

Trigger‐Associated Clinical Implications and Outcomes in Takotsubo Syndrome: Results From the Multicenter GEIST Registry

Abstract: Background Takotsubo syndrome is usually triggered by a stressful event. The type of trigger seems to influence the outcome and should therefore be considered separately. Methods and Results Patients included in the GEIST (German‐Italian‐Spanish Takotsubo) registry were categorized according to physical trigger (PT), emotional trigger (ET), and no trigger (NT) of Takotsubo syndrome. Clinical characteristics as well as outcome predictors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Long-term effects directly attributable to a TTS attack remain controversial due to the paucity of available data and concomitant presence of comorbidities, acute diseases and other confounding factors that can impact the outcomes within this heterogeneous population. Accordingly, multiple studies showed that patients with events triggered by emotional stress had better short and long-term outcomes compared with TTS secondary to physical triggers [7,10,16]. Scally et al [4] showed a reduction in peak VO 2 and VO 2 pulse and an increase in VE/VCO 2 slope at 20 (13-39) months from the index event in a heterogeneous population of 20 patients with previous TTS compared with matched control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term effects directly attributable to a TTS attack remain controversial due to the paucity of available data and concomitant presence of comorbidities, acute diseases and other confounding factors that can impact the outcomes within this heterogeneous population. Accordingly, multiple studies showed that patients with events triggered by emotional stress had better short and long-term outcomes compared with TTS secondary to physical triggers [7,10,16]. Scally et al [4] showed a reduction in peak VO 2 and VO 2 pulse and an increase in VE/VCO 2 slope at 20 (13-39) months from the index event in a heterogeneous population of 20 patients with previous TTS compared with matched control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline demographics and clinical data were collected, including ECG and echocardiographic presentation. Preceding trigger, if present, was recorded by the physician in charge at the time of hospital admission and reported as emotional, physical or absent as previously described [16]. Clinical, ECG and echocardiographic follow-up protocols in TTS patients at our Institution have been previously described [17].…”
Section: Methodsmentioning
confidence: 99%
“…TTS secondary forms, as previously defined ( 10 ), were considered when a physical trigger or emotional plus physical triggers were present. Primary forms were those without triggers or with an isolated identifiable emotional trigger ( 10 , 11 ). Right ventricular involvement was considered as such when any abnormality was demonstrated in the echocardiogram at that level and included in the clinical report.…”
Section: Methodsmentioning
confidence: 99%
“…These are not only “contributors” of the clinical picture of vulnerable HF patients typical of TTS, but, most importantly, are prognostic factors ( 8 , 12 , 14 , 16 ). Accordingly, TTS secondary to an emotional trigger has a relatively good prognosis, while physically triggered TTS has higher prevalence of non-CV comorbidities ( 17 ) and therefore is associated with worse outcomes ( 11 , 17 ).…”
Section: Why Talking About Cancer In Ttsmentioning
confidence: 99%
“…Similar frequencies were found in subsequent meta-analyses ( 18 , 26 , 27 ). In the three largest international TTS registries, cancer prevalence ranges from about 12% to 17% ( 17 , 28 , 29 ). Overall, cancer in TTS appears more common as compared to the general population, as well as to patients with AMI and HF ( 27 , 30 33 ).…”
Section: Impact Of Cancer On Tts Prognosismentioning
confidence: 99%